Gel Scaffolds of BMP‐2‐Binding Peptide Amphiphile Nanofibers for Spinal Arthrodesis. Issue 1 (22nd April 2014) - Lee, Sungsoo S.; Hsu, Erin L.; Mendoza, Marco; Ghodasra, Jason; Nickoli, Michael S.; Ashtekar, Amruta; Polavarapu, Mahesh; Babu, Jacob; Riaz, Rehan M.; Nicolas, Joseph D.; Nelson, David; Hashmi, Sohaib Z.; et al.
<x xml:space="preserve">Abstract</x> Peptide amphiphile (PA) nanofibers formed by self‐assembly can be customized for specific applications in regenerative medicine through the use of molecules that display bioactive signals on their surfaces. Here, the use of PA nanofibers with binding affinity for the bone promoting growth factor BMP‐2 to create a gel scaffold for osteogenesis is reported. With the objective of reducing the amount of BMP‐2 used clinically for successful arthrodesis in the spine, amounts of growth factor incorporated in the scaffolds that are 10 to 100 times lower than that those used clinically in collagen scaffolds are used. The efficacy of the bioactive PA system to promote BMP‐2‐induced osteogenesis in vivo is investigated in a rat posterolateral lumbar intertransverse spinal fusion model. PA nanofiber gels displaying BMP‐2‐binding segments exhibit superior spinal fusion rates relative to controls, effectively decreasing the required therapeutic dose of BMP‐2 by 10‐fold. Interestingly, a 42% fusion rate is observed for gels containing the bioactive nanofibers without the use of exogenous BMP‐2, suggesting the ability of the nanofiber to recruit endogenous growth factor. Results obtained here demonstrate that bioactive biomaterials with capacity to bind specific growth factors by design are great targets for regenerative medicine.